Future journalists’ fight against disinformation: analysis of university training offers and challenges in the Spanish context (Communication & Society, 2023)
Disinformation has become a global problem affecting mass media, governments and citizens globally. Besides the loss of trust in the media and its weakening influence, exposure to all manner of messages on social media in recent years has paved the way for disinformation, which has become a considerable challenge for journalism. According to the 2022 Edelman Trust Barometer, Spain is one of the countries most concerned about this phenomenon (Edelman, 2022). However, is this concern shared by Spanish journalist associations? What training initiatives are being carried out for future journalists to counter the spread of disinformation? How should fact-checking be taught in university? This study aims to answer these questions by using a dual methodology. First, a review and analysis were undertaken on the different training initiatives for bachelor’s and university-specific master’s degree students. Then, 15 in-depth interviews were conducted with experts, including fact-checkers, experienced journalists and representatives of sectoral associations, to ascertain their views on fact-checking and disinformation. The main results show that Spanish universities offer few training fact-checking-related initiatives, particularly at bachelor’s degree level, although more and more university-specific degrees and master’s degrees on this topic are becoming available. Furthermore, most interviewees view specialised training for the next generation of journalists as a key factor for fighting disinformation, and they provide guidelines to achieve this.